Subsidiary application of the norms of civil legislation to criminal-processoal relations - Фасій, Богдан Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article analyzes the current legislation of Ukraine, judicial practice regarding the application of the norms of civil legislation to criminal-procedural relations. The trial of a criminal case and a civil lawsuit were investigated.